Both reaching and grasping are impacted by temporarily induced paresthesia. (2nd April 2020) - Glazebrook, Cheryl M.; Brown, Kelsey; Prime, Steven L.; Passmore, Steven R.; Marotta, Jonathan J.
Abstract: Along with visual feedback, somatosensory feedback provides the nervous system with information regarding movement performance. Somatosensory system damage disrupts the normal feedback process, which can lead to a pins and needles sensation, or paresthaesia, and impaired movement control. The present study assessed the impact of temporarily induced median nerve paresthaesia, in individuals with otherwise intact sensorimotor function, on goal-directed reaching and grasping movements. Healthy, right-handed participants performed reach and grasp movements to five wooden Efron shapes, of which three were selected for analysis. Participants performed the task without online visual feedback and in two somatosensory conditions: 1) normal; and 2) disrupted somatosensory feedback. Disrupted somatosensory feedback was induced temporarily using a Digitimer (DS7AH) constant current stimulator. Participants' movements to shapes 15 or 30 cm to the right of the hand's start position were recorded using a 3 D motion analysis system at 300 Hz (Optotrak 3 D Investigator). Analyses revealed no significant differences for reaction time. Main effects for paresthaesia were observed for temporal and spatial aspects of the both the reach and grasp components of the movements. Although participants scaled their grip aperture to shape size under paresthaesia, the movements were smaller and more variable. Overall participants behaved as though they perceived they were performing larger and faster movements than they actually were. We suggest the presence of temporally induced paresthaesia affected online control by disrupting somatosensory feedback of the reach and grasp movements, ultimately leading to smaller forces and fewer corrective movements.